PARTISIPASI MASYARAKAT DALAM PROSES PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAH DESA (RPJMDES) (STUDI KASUS DESA ILOMANGGA KECAMATAN TABONGO KABUPATEN GORONTALO) - Fitria Lasangga; Ramlah Alkatiri; Sri Hantuti Paramata (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2026)
This study aims to determine community participation in the preparation of the Village Medium-Term Development Plan (RPJMDes) in Ilomangga Village, Tabongo District, Gorontalo Regency, and to identify the obstacles faced by the village government. This study uses a descriptive qualitative approach with interviews as the main research instrument involving informants relevant to the research problem. The findings show that community participation in the preparation process of the RPJMDes remains low and has not been optimal. Community participation is mostly represented through the Village Consultative Body (BPD), particularly through the active involvement of BPD members in village development planning. Viewed from the aspects of voice, access, and control, the wider community has not been directly involved in the overall planning process. Therefore, a more open, gradual, and participatory aspiration-gathering mechanism is needed.